Impact of Transfusing Packed Red Blood Cells Through a Rapid Infuser on Potassium Levels. Issue 1 (January 2023) - Metcalf, Ashley; Kitchens, Debra; Reddic, John; Liao, Wesley; Whitcomb, John; Wallenborn, Grace; Cull, John
Abstract : Background: Hyperkalemia is associated with the rapid transfusion of packed red blood cells in trauma patients. Rapid infusers can infuse blood up to 500 ml/min. Objective: This study aimed to determine whether infusing packed red blood cells through a rapid infuser impacts the potassium levels of the infused blood. Methods: Two baseline samples were obtained to measure potassium and hemolysis scores in 12 units of expired blood prior to infusion. The blood was then infused via the Belmont Rapid Infuser into collection bags at varying infusion rates (50, 100, 250, and 500 ml/min) utilizing different gauge catheter sizes (18-gauge, 16-gauge, and Cordis catheter). Two postinfusion blood samples were collected and tested for potassium and hemolysis scores and compared with preinfusion values. This process was then repeated with fresh blood. Results: The potassium levels of the samples taken from each unit prior to infusion (average difference 0.245) and after infusion (average difference 0.08) correlated well. There was no difference in potassium levels pre- and postinfusion at any infusion rate after accounting for catheter size and age of blood. The median potassium level of the fresh blood was 5.025 prior to infusion and 4.875 after infusion. The median potassium level of the expired blood was 16.05 prior to infusion and 16.4 postinfusion. There was no significant difference in the hemolysis scores between the preinfusion and postinfusion samples. Conclusions: Hyperkalemia in trauma patients undergoing massive transfusions is not a result of mechanical hemolysis from the high rates of blood infusion.